About the Cover Image. (1st March 2022) - Waling, Andrea; Power, Jennifer
Abstract : It was difficult to determine the right cover for this special issue. The purpose of the issue was to encourage new ways of thinking about the phallus, and the aim was to find an image that did just this—ask people to wonder what the image is telling us. What does it represent? What is the story? It is perhaps ironic that the image we found most appealing is a device designed to prevent a penis from functioning. In the late nineteenth century, masturbation was believed to cause mental illness, and solo ejaculation was considered a form of sexual dysfunction, and this is one example of many, often brutal, devices created to physically prevent erections and masturbation. Sitting over modern blue jeans, however, the image is erotic and evokes BDSM or kink culture. The old and the new, repression and eroticism, are one and the same.